Sustainable Amazonian Landcapes, Peru socioeconomic survey - Quintero, Marcela; Vanegas, Martha; Pérez Marulanda, Lisset; Camilo, Karen; Cruz García, Gisella S.; Sachet, Erwan; Sosa, Chrystian; Castañeda Álvarez, Nora P.; Romero Sánchez, Miguel Antonio; Soils, Reynaldo; Lao, Ceila (International Center for Tropical Agriculture, 2019)
The household survey was done in 35 communities that are part of the four landscape units from 17th June 2016 to 28th January 2017. A total of 417 households were surveyed. All the households that participated in the survey did it freely and under prior informed consent. Sampling was stratify across the four landscape units in order to take into account the different land uses that farmers give to the land according to the biophysics conditions of its land and this sample is also representative at community level. People surveyed usually were household heads or their spouses. The supervisors were the direct link with CIAT. The data was collected through Android Devices using the software CsPro 6.2 and 6.3, and the data analysis was done through the statistical software package Stata (StataCorp, 2013). (Reporte Interno: Linea Base Encuesta Socioeconomica Proyecto SAL, 2018) (2016)